Involvement of Activated Integrin α2β1 in the Firm Adhesion of Platelets onto a Surface of Immobilized Collagen under Flow Conditions - Moroi, Masaaki; Onitsuka, Ichiro; Imaizumi, Tsutomu; Jung, Stephanie M. (Thrombosis and Haemostasis, 2000)
Recently, we demonstrated that agonist-induced activation of the platelet surface collagen-receptor integrin α1 β2 converts it to an active form that can bind soluble collagen with high affinity (Jung, SM, Moroi, M: J Biol Chem 1998; 273: 14827-37). Here, the involvement of α2 β1 activation and the high affinity binding property of activated α2β1 in platelet adhesion to a collagen surface under flow conditions were analyzed. Platelet adhesion to immobilized collagen was measured in the presence of TS2/16, an activating anti-integrin α2β1 antibody, and inhibiting antibodies, Gi9 and 6F1. TS2/16 decreased the moving velocity of platelets on the collagen surface, but Gi9 and 6F1 increased it, indicating that α2β1 activation induces the tight binding of platelets to immobilized collagen under flow. Platelet adhesion, expressed as the surface area occupied by adhered platelets, in the presence of TS2/16 was similar to that in its absence. In contrast, adding Gi9 or 6F1 caused biphasic adhesion composed of a first phase, a lag phase whose length differed in each experiment, and a second phase adhesion with a rate similar to that of the control. This biphasic adhesion indicates that α2β1 activity is inhibited and also suggests that some other factor(s) may contribute to the adhesion under flow. At concentrations where neither 6F1 nor Gi9 affected collagen-induced aggregation, these antibodies inhibited soluble collagen binding to thrombin-activated platelets. Only at much higher concentration did 6F1 inhibit collagen-induced aggregation. TS2/16 had no effect on the aggregation. The present results are evidence against the major involvement of integrin α2β1 in platelet aggregation; instead, they indicate that integrin α2β1 would be mainly associated with the tight binding of platelets to collagen.
Keywords: Integrin α2β1; platelet; flow adhesion; collagen